The difficult discussion on the deactivation of implantable cardioverter devices at the end of life: a systematic review - Siobhan C. Murray; Claire McNamara; Anna V. Chatzi (ESC Heart Failure)
Abstract Implantable cardioverter defibrillators (ICDs) reliably prevent death due to life‐threatening arrhythmias; this may become less relevant in people with more severe heart failure who are reaching the end of life (EOL). This review aimed to explore the ICD deactivation process and identify ethical issues, especially around the initiation of relevant discussions among professionals and patients. Available literature was reviewed using four electronic databases to identify issues that may deter healthcare professionals from having important deactivation discussions and to address considerations for ICD management prior to the EOL. The search resulted in the retainment of 12 studies. Three themes emerged from the data: barriers and facilitators, ethical considerations in clinical practice, and nurse's role. Lack of knowledge, which has been associated with cultural differences, has been found among the barriers, and interdisciplinary education and open communication appeared as facilitators. As clinicians' ethical considerations and fears emerged from the literature, nurses' special role has not been sufficiently supported. Complex care requires facilitation by multidisciplinary teams and education around the device's function regarding EOL issues. Establishing expert consensus statements on advance care planning might help define the distinct roles of each healthcare practitioner involved. Further research is needed in addressing the identified gaps.